The Strategy of Negative Representation of “Others” in Political Discourse: Tactics of Implementation - Kalishchuk, Diana (East European Journal of Psycholinguistics, 2014)
The article deals with the analysis of the strategy of negative presentation of “others” as local strategy within the global discourse strategy. The strategy of influence is considered to be the global strategy of political discourse. Persuasiveness is considered to be a universal property of political discourse and it manifests itself in form of speech manipulation. Political manipulation is treated as specific type of influence. The author interprets manipulation as peculiar communicative speech strategy, to realize which the speaker chooses certain methods and tactics and selects certain language means. The most common local strategies are the strategies of positive self-presentation and negative presentation of “others”. The paper outlines the tactics to realize the strategy of negative presentation of “others”, namely such tactics as super-generality, exemplification, transposition and attribution, which are considered to be the most common ones. Although no language means are meant to be used for manipulation, the research has proved that almost any language means may be used for that. References Chernyavskaya, V. (2006). Diskurs Vlasti i Vlast’ Diskursa: Problemy Rechevoho Vozdeystviya [Power Discourse and Power of Discourse: Issues of Speech Influence]. Moscow: Nauka. Dijk, Teun A.van (2013). Discurs i Vlast’: Representatsiya Dominirovaniya v Yazyke i Komunikatsii [Discourse and Power: Representation of Dominance in the Language and Communication]. Moscow: LIBROKOM. Gronskaya, N. (2003). Yazykovyie mekhanismy manipulirovaniya massovym politicheskim soznaniyem [Speech mechanisms of mass political consciousness manipulation]. Lobachevsky Nizhniy Novgorod University Journal, 1, 220-231. Golodnov, A. (2003). Lingvoprogmaticheskiye osobennosti persuazivnoy kommunikatsii (na primere sovremennoy nemetsoyazychnoy reklamy) [Lingvo-pragmatic peculiarities of persuasive communication]. St.Petersburg Dotsenko, Ye. (2004). Psikhologiya Manipulyatsii: Phenomeny, Mekhanismy i Zashchita [Psychology of Manipulation: Phenomena, Mechanisms and Defence]. St.Petersburg : Rech. Issers, O. (2006). Kommunikativniye Strategii i Taktiki Russkoy Rechi [Communicative Strategies and Tactics of the Russian Language]. Moscow: KomKniga. Leontyev, A. 2003) Psycholynhvystycheskaya Ekspertiza Ksenofobii v Sredstvakh Massovoi Informatsii [Psycholinguistic Expert Analysis of Xenophobia in Mass Media]. Moscow: Smysl. Martyniuk, A. (2009). Dyskursyvny instrumentariy analizu anhlomovnoyi reklamy [Discourse instruments of English advertisements]. Lingvistika XX stolittya: Novi Doslidzhennya i Perspektyvy, 3, 159-167. Zasiekina, L. & Zasiekin, S. (2008). Psykholinhvistychna Diagnostyka [Psycholinguistic Diagnostic]. Lutsk: Vezha. Sources Barack Obama Speech on Bush, McCain, War and Appeasement in Watertown, South Dakota. May 16, 2008. Retrieved 21.09.2014 from: http://irregulartimes.com/index.php/ archives/2008/05/16/text-transcript-of-barack-obama-speech-on-bush-mccain-war-and-appeasement- inwatertown-south-dakota-on-may-16-2008/ Hillary’s Remarks on Super Tuesday. February 5, 2008. Retrieved 21.09.2014 from http://www.cfr.org/us-election-2008/clintons-speech-super-tuesday/p15446 Interview with the New York Post Editorial Board. Secretary Condoleezza Rice. September 15, 2006. Retrieved 21.09.2014 from: http://2001-2009.state.gov/secretary /rm/2006/73107. htm President Addresses Nation, Discusses Iraq, War on Terror. – 2005. Retrieved 18.09.2014 from: http://georgewbush-whitehouse.archives.gov/news/releases/2005/06/20050628-7.html President Bush Participates in Joint Press Availability with Prime Minister Gordon Brown of the United Kingdom. – 2007. Retrieved 18.09.2014 from: http://www.whitehouse.gov/news/releases/2007/07/text/20070730.html President Obama’s Full Campaign Kickoff Speech. May 05, 2012. Retrieved 21.09.2014 from: http://articles.latimes.com/2012/may/05/news/la-pn-transcript-obama-campaign-kickoff20120505 State of the Union 2012. Retrieved 18.09.2014 from: http://www.washingtonpost.com/ politics/state-of-the-union-2012-obama-speech-excerpts/2012/01/24/gIQA9D3QOQ_story.html